2019
DOI: 10.1124/jpet.118.252833
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Tubule β2-Adrenergic Receptor Mediates Formoterol-Induced Recovery of Mitochondrial and Renal Function after Ischemia-Reperfusion Injury

Abstract: Acute kidney injury (AKI) is the transient loss of renal function following an insult, such as nephrotoxicant exposure, sepsis, or ischemia. Numerous cell types play a role in the pathogenesis of AKI, including immune, endothelial, and renal proximal tubule cells. Our laboratory demonstrated that the beta‐2 adrenergic receptor (ADRB2) agonist formoterol accelerates the recovery of renal and mitochondrial function in mice following ischemia‐reperfusion injury (IRI). However, the cell type(s) responsible for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…As reported in Figure 2A, the expression of PGC1α protein (Peroxisome Proliferator-Activated Receptor-Gamma Coactivator-1α), a transcriptional coactivator that regulates the genes involved in energy metabolism and a master regulator of mitochondrial biogenesis, was similar between groups. We further confirmed this finding by testing for another mitochondrial biogenesis factor (Gibbs et al, 2018;Cameron et al, 2019) -the mitochondria DNA content (mtDNA copy number) in the renal cortex by qPCR. As demonstrated in Figure 2B, this experiment did not reveal differences in the mitochondria-encoded Nd1 and Nd6 gene expression (normalized to genomic DNA encoded Actb).…”
Section: Dietary Salt Challenge Does Not Affect Mitochondrial Biogenesupporting
confidence: 64%
“…As reported in Figure 2A, the expression of PGC1α protein (Peroxisome Proliferator-Activated Receptor-Gamma Coactivator-1α), a transcriptional coactivator that regulates the genes involved in energy metabolism and a master regulator of mitochondrial biogenesis, was similar between groups. We further confirmed this finding by testing for another mitochondrial biogenesis factor (Gibbs et al, 2018;Cameron et al, 2019) -the mitochondria DNA content (mtDNA copy number) in the renal cortex by qPCR. As demonstrated in Figure 2B, this experiment did not reveal differences in the mitochondria-encoded Nd1 and Nd6 gene expression (normalized to genomic DNA encoded Actb).…”
Section: Dietary Salt Challenge Does Not Affect Mitochondrial Biogenesupporting
confidence: 64%
“…Some drugs acting on adrenergic receptors, such as AD and isoproterenol, can induce myocardial injury [ 20 , 21 ]. Reduced β-adrenergic receptor (β-AR) responsiveness could improve liver damage and myocardial injury [ 22 ], and a β2-adrenergic receptor (β2-AR) agonist could aid in the recovery of ischemia–reperfusion injury [ 23 ]. SNP is a donor of NO; therefore, we established an excessive NO damage model induced by SNP to study the role of the adrenergic system in nerve injury [ 24 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Formoterol, a long-acting β2 selective agonist, was shown to improve the recovery of renal function after acute kidney injury (AKI) by activating proximal tubule β2AR and inducing mitochondrial biogenesis. 28,29 A recent study reported the prognostic significance of renal β2AR expression in clear cell renal cell carcinoma where reduced β2AR levels were associated with poor prognosis. 30 Excessive lipid accumulation in renal cells is an established mechanism of renal injury.…”
Section: Discussionmentioning
confidence: 99%